The use of Maternal and Child Health (MCH) handbook improves healthy behavior of pregnant women - Nur Hidayatul Ainiyah; M Hakimi; Anjarwati Anjarwati (Majalah Obstetri dan Ginekologi, 2017)
Objectives: To investigate correlation between maternal and child health (MCH) handbook utilization and healthy behavior of trimester III pregnant women.Materials and Methods: This study used Spearman-Rho non-parametric correlation test with 95% of the Power of Test.Results: The correlation between MCH utilization and the healthy behavior of trimester III pregnant women showed correlation coefficient (r) of 0.530 and CI 95% 0.163-0.638, indicating middle level of correlation with p-value of 0.01 (p<0.05), showing statistical significance.Conclusion: MCH (maternal and child health) handbook utilization improves healthy behavior of trimester III pregnant women. The higher the utilization of MCH, the healthier the behavior of trimester III pregnant women.